An Analysis of Conceptual Metaphor in Helena Natasha's Dreams, Spelled in Poetry - Safira, Rizqiyah (Journal of Literature, Linguistics, & Cultural Studies, 2022)
This study aimed to identify the widely used metaphors and analyze the meanings that construct the reality of 'life' in the literary work entitled Dreams, Spelled in Poetry (2021) by Helena Natasha. Poetry data taken were a collection of poems with the theme 'The Call.' The method used by the researcher was descriptive qualitative by combining two theories; first, to identify the types of metaphors used by the poet in the poem with the theme 'The Call' and to analyze the conceptual metaphors that shape reality the researcher used the theory of Lakoff and Johnson (2003) and second, to identify the 'life' reflected in the researcher's poetry the researcher used the theory of Kovecses (2007). Correspondence elaboration or concept mapping was used to conceptualize the relationship between the source domain and the target domain to construct the reality of 'life.' This study tried to conduct a cognitive semantic study of the concept of life in Helena Natasha's poetry from the perspective of cognitive linguistics. The analysis results showed that the type of metaphor used by Helena Natasha in the poem with the theme ‘The Call’ was dominated by ontology metaphors with fifteen data. Furthermore, the author managed to find two concepts contained in the poem with the theme ‘The Call’ that succeeded in shaping the reality of 'life,' namely, 'ambition is fire/light', and 'life is a journey'.